Raw Algerian Calcic Clay as a Sustainable Adsorbent for Pesticide Removal - Imene, Feddal; Imad Eddine, Ben Arraba; Abdelhak, Mesbah; Goussem, Mimanne (Bulletin of Chemical Reaction Engineering & Catalysis, 2026)
Pesticides are widely used around the world to control weeds in order to increase agricultural production. Classically, herbicides applied in excess in fields cause serious problems and during their application, they can lead to the loss of biodiversity. In the present work, we try to study the adsorption of diuron in an aqueous solution on the calcic clay Diuron is a phenyl derivative herbicide widely used in agricultural work Diuron is a phenyl derivative herbicide widely used in agricultural work persists in soil and ground and surface water. , some analysis and characterization were done. Adsorption of diuron was done using raw calcium clay. The study of the adsorption allows to optimize some parameters influencing this process: contact time, mass of the adsorbent, pH, temperature, and the modeling of adsorption isotherms of which those used are: Langmuir, Freundlich, Temkin and Elovich. The results obtained show that the adsorption reaction of diuron on raw calcium clay is an exothermic process, the removal of diuron agrees with the Freundlich model.